X-ray perception: Animal studies of sensory and behavioral responses to X-rays - Mantraratnam, Vaishnavi; Bonnet, Jorge; Rowe, Caleb; Janko, Daniel; Bolding, Mark (Frontiers in Cellular Neuroscience, 2022)
Since their discovery, many studies have been conducted to understand the effect of X-rays on the neural function and behavior of animals. These studies have examined a broad range of acute and chronic effects and a subset of studies has attempted to determine if X-rays can produce any sensory responses. Here we review literature from the discovery of X-rays in 1895 until the present to better understand the chronology of studies of acute X-ray behavioral effects in animals and to assess the evidence for the detection of X-rays by sensory receptors in animals. We focus on the changes in appetitive and consummatory behavior, radiotaxis, behavioral arousal, and olfactory responses to X-rays that have been reported in the literature. Taken together, the reviewed literature provides a large body of evidence that X-rays can induce sensory responses in a wide variety of animals and also suggests that at least some of these responses are mediated by sensory receptors.